Herpes-like impetigo due to group A ß-haemolytic Streptococcus. - Patrizi, A.; Savoia, F.; Giacomini, F.; Neri, I. (European Journal of Pediatric Dermatology, 2007)
Patients affected by atopic eczema very often present skin overinfection. The more frequently involved bacterium is Staphylococcus aureus, whereas only rarely group A ß-hemolytic Streptococcus is cultured from the overinfected areas of atopic eczema. We present two patients affected by atopic eczema with herpes-like lesions caused by group A streptococcal infection. Clinicians should be aware of this condition to institute a correct empirical therapy prior to microbiological confirm of the infectious agent.